Avaliação clínica e mecânica de protocolos mandibulares com número de implantes reduzido - Cavalcante, Luisa de Andrade Lima (2018)
The Branemark® protocol made possible a new modality of treatment for edentulous individuals: Fixed implant prostheses. But for physical or economic reasons this treatment is not accessible to many people. As an alternative, complete fixed mandibular prosthesis supported by three implants have been performed. Studies indicate that this alternative is promising, but are still few the knowledge of the clinical results and the consequences of the different configurations of this type of rehabilitation. In this way, it seems appropriate to follow the results of fixed total mandibular rehabilitations on three implants and investigate the consequences of their different configurations. This study involved follow-ups to investigate the clinical results and satisfaction of patients after one year and after 5 years of prosthesis and evaluation of deformation of different configurations of this type of rehabilitation. The methodologies used were: clinical analysis of prostheses, radiographic analysis of implants, application of a questionnaire to know patient evaluation and extensometry tests. Clinical results showed high patient satisfaction rates; high success rates of implants and prostheses; bone levels of the straight implants were worse than those of the angled implants and the most frequent complications were the screw loosening and fracture of the resin portion of prostheses. The laboratory results indicated that the different inclinations of the distal implants (straight, 17º and 30º) in fixed mandibular rehabilitations on three implants do not generate significant changes in the deformation in the infrastructure and / or the model, and that the place of application of load on the implant cantilever influences significantly the deformation in the infrastructure.